Boosting efficiency and stability of a Cu2ZnSnS4 photocathode by alloying Ge and increasing sulfur pressure simultaneously. (November 2017) - Wen, Xin; Luo, Wenjun; Guan, Zhongjie; Huang, Wei; Zou, Zhigang
Abstract: Cu2 ZnSnS4 (CZTS) is a very promising absorber for solar driven photovoltaics and water splitting applications due to its high theoretical efficiency, low-cost and non-toxicity. Alloying Ge into CZTS is a potential method to improve the efficiency of CZTS-based devices. However, decomposition of Ge-CZTS during a high temperature sulfurization process usually leads to serious Ge element loss and secondary phases, which lower the performance of Ge-CZTS based devices. Moreover, inconsistent optimum Ge content over a wide range was reported in previous studies. To date, there is no reasonable explanation on this unusual phenomenon. In this study, for the first time, we found that an optimum Ge content sensitively depended on sulfur pressure. By increasing sulfur pressure and alloying Ge simultaneously, a high crystalline Ge-CZTS without Ge element loss and secondary phases was obtained, which remarkably increased a half-cell solar to hydrogen efficiency (HC-STH) of a CZTS photocathode 27 times. After further modification, the Ge-CZTS photocathode indicated a stable photocurrent density of 11.1 mA cm −2 at 0 VRHE . To the best of our knowledge, it is the highest value among CZTS based photocathodes for solar water splitting. Moreover, the stability of a CZTS photocathode was also improved by increasing sulfur pressure and alloying Ge simultaneously due to higher crystalline of Ge-CZTS film. Graphical abstract: By alloying Ge and increasing sulfur pressure simultaneously, a 27-fold improvement on half-cell solar to hydrogen efficiency (HC-STH) is achieved in a Ge alloyed Cu2 ZnSnS4 (Ge/(Ge+Sn) = 0.25) photocathode for solar water splitting. Highlights: A sulfur pressure dependent optimum Ge content in Ge-CZTS is found for the first time. The Ge-CZTS photocathode indicates a photocurrent density of 11.1 mA cm −2 at 0 VRHE, which is the highest among CZTS based photocathodes. The stability of Ge-CZTS photocathode is largely improved due to high crystalline. This is a new preparation strategy for pure Ge-CZTS and offers guidance to produce other compounds with highly volatile elements.